Humanistic care in nursing: Concept analysis using rodgers' evolutionary approach - Fakhredin Taghinezhad; Eesa Mohammadi; Mojgan Khademi; Anoshirvan Kazemnejad (Wolters Kluwer Medknow Publications, 2022)
Background: Despite the importance and prominent role as a clinical, theoretical, and research approach in nursing practice, humanistic care nature and boundaries are not explicit and challenging for nurses to understand. This study was conducted to clarify the concept of humanistic care in nursing. Materials and Methods: Based on Rogers's evolutionary concept analysis, keywords such as "humanistic car *," "caring behave *," "humanistic nurs *," "humanistic model of care," were searched in PubMed, SCOPUS, Science Direct, Web of Science, WILEY, Springer, SAGE, ProQuest, SID, Iranmedex without time limit until November 2018. Sixty-five documents in nursing and ten documents in the medical discipline were finalized for thematic analysis. Results: Nine attributes of the humanistic care, including "excellence in clinical literacy," "creating a healing environment," "a comprehensive and unique viewpoint," "contribution to clients' adaptation and flourishing of their talents," "unrequited love and affection," "preservation of human dignity," "real presence," "constructive dynamic interaction," and "nurse's self-care," were recognized. Assessing the historical and evolutionary course of the concept's semantic tendency revealed three periods: The focus in first, second, and third was on the nurse-patient relationship, quantitative tendency/measurement, and metaphysics/spiritual humanism, respectively. The comparison of interdisciplinary differences indicated greater semantic comprehensiveness and depth in the nursing discipline. Conclusions: Clear and practical definition and identification of humanistic care in nursing can be helpful in the further development of existing knowledge, instrumentation, designing guidelines, clinical interventions, knowledge translation, and correction of concept misuse. The identified antecedents and consequences can be in various aspects of clinical management.